Implementation of SORA Methodology Version 2.5 for Medical Delivery Using Quadrotor UAS in Remote Areas - Hidayat, Rachmad; Jenie, Yazdi Ibrahim (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2023)
The innovative quadrotor Unmanned Aircraft Systems (UAS) approach for delivery missions presents significant opportunities to address logistical distribution challenges (i.e. medical delivery) in remote areas. The efficiency of quadrotor UAS, which does not need additional infrastructure like runways, makes it increasingly applicable to remote regions. However, the potential implementation of UAS for medical delivery missions comes with considerable risks, such as collisions with manned aircraft or UAS crashes that could damage infrastructure and cause fatal injuries to human life. Therefore, in UAS operations, a method of operational risk assessment is needed to ensure safety, resilience, and operational success. The Joint Authorities for the Rulemaking of Unmanned Systems (JARUS) offers a risk assessment methodology named Specific Operational Risk Assessment (SORA) for UAS operations. The European Union Aviation Safety Agency (EASA) and the Indonesian Ministry of Transportation have recognised and approved this methodology as a risk assessment method for specific UAS categories. SORA provides a step-by-step framework in risk assessment to identify, evaluate, and determine necessary mitigation actions to achieve an acceptable means of compliance (MoC). EASA has announced using the latest version, SORA V2.5, planned for implementation in the fourth quarter of 2023. The Indonesian Ministry of Transportation also plans to adopt this latest version for UAS operations. Several updates and simplifications have been made to this version. Therefore, this paper presents the application of risk assessment using SORA V2.5 for medical delivery operations in remote areas using quadrotor UAS. The analysis in this paper covers each step of SORA V2.5, including risk identification and evaluation, as well as the implementation of mitigations in the conducted mission. The results indicate that SORA V2.5 can be implemented in this mission by taking appropriate mitigation actions to assure operational safety. There are also recommendations for optimising risk identification and it can complement the SORA methodology.